2020
DOI: 10.33920/sel-09-2010-02
|View full text |Cite
|
Sign up to set email alerts
|

Results of ichtiological studies in the deep-water section of the Yellow River — a potentially possible winter pit

Abstract: Wintering pits of semi-passable and river fish on the Lower Volga have historically had a protected status that prohibits any fishing in their waters. The wintering period is important in the life of semi-migratory and river fish, and directly affects the formation of their stocks. The process of pit formation in the Volga Delta is continuous. At the same time, some of the pits lose their fishing significance over time, while others, newly formed, on the contrary, have mass accumulations of fish, especially in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…According to the researches of many authors, it has been noted that certain characteristics of the depth and near-bottom current velocities are fundamentally necessary conditions for the habitat of fish in the winter. [10,29,34]. Using the example of sturgeons, it was shown that [10] both depth and near-bottom flow velocity are important predictors of the choice of habitat for wintering fish.…”
Section: Discussionmentioning
confidence: 99%
“…According to the researches of many authors, it has been noted that certain characteristics of the depth and near-bottom current velocities are fundamentally necessary conditions for the habitat of fish in the winter. [10,29,34]. Using the example of sturgeons, it was shown that [10] both depth and near-bottom flow velocity are important predictors of the choice of habitat for wintering fish.…”
Section: Discussionmentioning
confidence: 99%